Prospective Memory Performance in Persons With Schizophrenia and Bipolar Disorder and Healthy Persons. Issue 4 (4th July 2016) - Au, Raymond W. C.; Xiang, Yu‐Tao; Ungvari, Gabor S.; Lee, Edwin; Shum, David H. K.; Man, David; Tang, Wai‐Kwong
Abstract : PURPOSE: There is a paucity of studies comparing prospective memory (PM) impairment between persons with schizophrenia and bipolar disorder . The aim of this study was to directly compare PM performances of these two groups and healthy controls. DESIGN AND METHODS: A total of 44 persons with schizophrenia and 76 with bipolar disorder, and 44 healthy controls formed the study sample. FINDINGS: Patients were found to be impaired in PM relative to controls and the two patient groups showed similar level of PM performance after controlling confounding sociodemographic and clinical variables. PRACTICE IMPLICATIONS: The findings add to the evidence concerning the neurocognitive similarity between cohorts of schizophrenia and bipolar disorder with respect to PM. Rehabilitative effort in PM remedies for both patient groups is warranted.